Remote Sensing and Geographic Information System based Agroforestry Suitability Mapping and Area Identification in Part of Jharkhand - Ahmad, Firoz; Goparaju, Laxmi; Qayum, Abdul (Indian Forester, 2018)
Agroforestry has tremendous potential for poverty alleviation, alternate food security instrument and attempts to improve quality of fallow and abandoned land. Nonetheless, with advent of new technologies the practices of agroforestry can be scaled up as technology potentially predicts areas which have relatively higher suitability. Satellite data harnessed through remote sensing and maneuvered through GIS offers a better decision support system and prioritization of forest area for higher productivity. The present study aims for identification of suitable area for agroforestry projects towards maximizing the outcome in terms of agriculture output and carbon sequestration capacity by generating integrated maps for Chakardharpur sub-division, West Singhbhum district of state of Jharkhand. A weight matrix was derived based upon field data and related research works to produce nitrogen, phosphorous, potassium mapping along with soil pH, organic carbon and sulphur content. Later, it was superimposed with remote sensing imageries/images, topographic maps and climatic datasets for integrated mapping in GIS to develop agroforestry suitability. It was found that 21.6 % areas have high suitability and within watersheds 22 sample points corresponding to some village was generated for making buffers. It was done to establish relationship of nearness of watershed areas with high suitability. The study highlighted the scope of geo-spatial technology agroforestry practices and in estimating prominent factors for its optimal productivity. It demands for diversions of forestry projects of areas which plunge in high suitability zones to optimize the outcome. The use of ancillary data in GIS domain can have gigantic potential to map the land and emerging as one significant dimension in food security and carbon sequestration targets.